Industrially beneficial microbes from kitchen waste: A green approach to produce Cellulase Enzyme and optimization of culture condition - Islam, Tanha Hasin; Ferdous, Zahan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.